PELAKSANAAN KEWAJIBAN ZAKAT BAGI PEGAWAI NEGERI SIPIL YANG BERAGAMA ISLAM DALAM LINGKUNGAN UNIVERSITAS NEGERI MAKASSAR - Mustaring Mustaring; Muh. Sudirman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
This study aims to determine the understanding of Civil Servants (PNS) who are Muslims in the Makassar State University environment about the Law of Zakat and how it is implemented. The method that will be used to achieve the objectives in this study is a qualitative descriptive approach. Through this approach, this research will describe the actual situation in detail and actual. The background to the use of this method, because the phenomena to be investigated require a description or description and deep analysis. Thus, answers will be found that can reveal actual events or facts in the field. This approach is suitable for expressing unique social phenomena, because this approach is flexible and not strict so that many alternatives can be used to answer a phenomenon that is happening in the field. This research is planned to be carried out in the Makassar State University environment. It will begin with conducting observations to determine the research objectives, while studying the conditions in the field. Furthermore, data collection will be carried out, both primary and secondary data. The primary will be collected using questionnaires, interviews and documentation.